Perlindungan Hukum Terhadap Nasabah Dalam Perjanjian Penawaran Produk Asuransi Bank Melalui Telemarketing (Studi PT. BNI Life) - Astriani Budi Lestari; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2022)
This research has the purpose to find out the legal relations between the parties like guarantor (bank) and insured (customer) through telemarketing offering bank insurance to the customers. This bank insurance is an agreement to give rights and duties to the parties. The type of this research is normative-empirical legal research which uses the statute approach, the conceptual approach, and the sociological approach. Based on the result of this field study, the study showed that there are problems like the bank not clearly explaining the insurance products when they offered to the customers. The legal protection for the bank customers regulated in Act Number 8 of 1999 concerning Consumer Protection and Financial Services Authority Regulation Number 23/POJK.05/2015 concerning Insurance Product and Insurance Product Marketing.